GROWTH AND YIELD OF RABI GROUNDNUT (ARACHIS HYPOGAEA L.) AS INFLUENCED BY MOISTURE REGIMES, POLYTHENE MULCH AND PLANT DENSITIES - ZAGADE, M.V.; CHAVAN, S.A. (Annals of Agricultural Research, 2014)
A field trail to study the effect of growth wise irrigation regimes, mulching and plant densities on growth and yield attributing characters and yield of rabi groundnut was conducted at College of Agriculture Farm, Depoli, Distt. Ratnagiri. (M.S.) during rabi season of 2001-02 and 2002-03. Results based on pooled data indicated that growth wise irrigation scheduling at 0.6:1.0:0.8 IW/CPE ratios recorded significantly higher per plant growth in terms of height, number of leaves, branches and dry matter accumulation, from 60 days after sowing (DAS) to harvest (120 DAS) and subsequently the per plant yield parameters such as number and weight of mature pods, kernels and 100 kernel weight, shelling percentage ; which resulted into significantly higher dry pod and haulm yield overall other irrigation treatments. Similarly, polythene mulch recorded significantly higher growth, attributing characters from 30 DAS upto harvest and subsequently the yield attributing characters and yield, as compared to no mulch treatment. Further, the lower plant density (4,44,444 plant ha-1) produced significantly higher growth, yield attributing characters refered above and yield of groundnut, over higher plant density (5,55,555 plant ha-1) except in case of height that was significantly higher under the higher plant density than the lower plant density.